Three-dimensional composite copper foil and preparation method thereof

Through formaldehyde-free wet electroless copper plating method combined with electroplating method, composite copper foil with three-dimensional interconnection structure was prepared, which solved the problems of complex process, high cost and limited structure in the prior art, and achieved high energy density, long cycle life and high safety performance battery current collectors.

CN119560567APending Publication Date: 2025-03-04ADVANCED ENERGY SCIENCE & TECHNOLOGY GUANGDONG LABORATORY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411308513.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing composite copper foil has complex preparation process, high cost, and limited structure, making it difficult to further reduce the thickness of the copper foil to increase the energy density of the battery.

Method used

Formaldehyde-free wet electroless copper plating method combined with electroplating method was used to prepare composite copper foil with three-dimensional interconnection structure, which solved the problem of structure and size limitations, and improved conductivity and heat dissipation.

Benefits of technology

It realizes a three-dimensional composite copper foil with a solid structure, small resistivity, fast heat dissipation and high safety performance, which improves the energy density of the battery cell and improves the circulation and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560567A_ABST
    Figure CN119560567A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional composite copper foil and a preparation method thereof. The three-dimensional composite copper foil comprises a porous membrane substrate and a three-dimensional copper structure deposited on the porous membrane substrate, according to the formaldehyde-free wet chemical copper plating method, sodium hypophosphite is adopted as a reducing agent, and copper on the surface and pore walls of the porous membrane substrate is metalized; the three-dimensional copper structure comprises copper layers distributed on the two sides of the porous membrane substrate, and solid copper structures which are filled in pore channels of the porous membrane substrate and are connected with the copper layers; the porous membrane base body is provided with a plurality of pore channels penetrating in the thickness direction, and the pore channels can be straight-through or bent. The three-dimensional composite copper foil is firm in structure, small in resistivity, fast in heat dissipation and high in safety performance, the energy density of a battery cell can be improved, and the cycle and rate performance of a battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of current collectors, and in particular to a three-dimensional composite copper foil and a preparation method thereof and a current collector. Background Art

[0002] Lithium-ion batteries are currently the most widely used secondary batteries due to their many advantages such as high energy density, high specific capacity, and long cycle life. With the rapid development of the economy, lithium-ion batteries have been continuously improving their energy density and applied to large-scale energy storage needs. There are two main ways to increase the energy density of batteries. One is to find other active material systems that can increase the energy density, and the other is to reduce the proportion of inactive substances to make the battery lighter and increase the proportion of active substances. Among them, the main implementation path of the second method is to optimize and improve each component of the battery to improve the various performance of the battery.

[0003] As one of the important components of lithium batteries, the current collector plays an important role in maintaining power transmission between the electrode and the external circuit. Although the current collector is an inactive substance, a slight improvement in the current collector can greatly affect the electrochemical performance of the battery. The traditional battery negative electrode current collector is a copper metal foil with a high density, which accounts for a large proportion of the weight in the battery. Therefore, reducing the mass of the copper current collector is also one of the effective ways to lighten the battery. Through nearly 20 years of efforts, the thickness of copper foil has been reduced from the initial 20μm to the current 4.5-6μm. However, blindly reducing the thickness of the current collector will further increase the manufacturing cost, and its poor mechanical properties are not suitable for industrial production and application. The thickness of copper foil has almost been reduced to the limit, so it is imperative to explore new materials and structures to reduce the mass of the current collector. Since the composite current collector can effectively reduce its mass while maintaining good mechanical properties, it has attracted much attention in recent years.

[0004] Composite copper foil is a sandwich structure of "copper metal-polymer material-copper metal", with polymer materials such as PET, PP, PI as the middle layer, and copper metal deposited on the upper and lower sides. Polymer materials have good ductility and can effectively relieve the local compressive stress caused by lithium dendrite growth through slight deformation (such as wrinkles) during use to increase battery safety, and its lower density can effectively reduce the mass of the current collector to increase the battery energy density. Composite copper foil has become the development direction and research focus of battery negative electrode current collectors due to its advantages of high safety, high specific energy, long life, and low cost.

[0005] The key to preparing composite copper foil lies in the copper metallization of the polymer material layer. The current preparation methods of composite current collector copper foil mainly include magnetron sputtering + water electroplating, extrusion molding or the use of binder + magnetron sputtering. For example, patent CN214476458U proposes a multi-layer composite copper foil for lithium battery current collector, which is deposited on an ultra-thin PET film by vacuum magnetron sputtering, and then a porous film with a metal layer on the pore wall is composited and a flame retardant material is filled in the pores. Finally, a metal film is deposited on the surface of the porous film using vacuum magnetron sputtering technology to obtain a multi-layer composite copper foil with flame retardant properties. However, the composite copper foil prepared by vacuum magnetron sputtering and vacuum coating has a relatively complex process and high cost, which limits its industrial application to a certain extent. Patent CN114161787A reports a composite copper foil technology, which is formed by extrusion molding on two sides of a hot-melt insulating resin. A layer of copper foil is pressed on each side, and then the semi-finished copper foil is reduced in weight according to the demand to obtain a composite copper foil with thinner thickness on both sides. Although the process of extrusion molding is relatively simple, it is difficult to further reduce the thickness of the copper foil, and the improvement of the battery energy density is limited; Patent CN116031412A discloses a memory current collector, which is first prepared by thermal spraying or vapor deposition on the upper and lower surfaces of the polymer film to prevent the metal coating from falling off, and then the bonding layer is subjected to hot pressing, plasma spraying, electrostatic spraying, anilox coating, vacuum coating, thermal spraying, vapor deposition or water electroplating to prepare the metal coating. The composite current collector is prepared by a method. Although the patent uses a metal binder to increase the binding force of the metal layer, a series of side reactions of the binder during use after the introduction of the negative electrode will affect the rate and cycle performance of the battery, and the non-metallic binder will also affect the conductive properties of the current collector. From the perspective of the technology disclosed in the existing patents, the preparation of composite copper foil is mainly concentrated in the physical method, which has great limitations. Therefore, it is possible to develop a chemical method for preparing lightweight composite copper foil. Chemical copper plating usually requires formaldehyde as a reducing agent and needs to be carried out at a higher pH value. Due to the corrosive effect of alkali, there are certain limitations on the substrate, and there are problems such as toxic formaldehyde vapor volatilization and low stability of the plating solution during the plating process. Therefore, the use of formaldehyde-free wet chemical copper plating is now advocated.

[0006] In addition, the sandwich structure of ordinary composite copper foil also has some inherent defects. The structure of ordinary composite copper foil is compounded by weak intermolecular bonding force, which makes the metal layer easy to fall off during use, causing the capacity of the battery to decay and the performance to decline; the polymer material layer completely separates the thin copper layer on both sides, which increases the surface resistance of the current collector to a certain extent, and also reduces the heat dissipation capacity of the current collector, causing the safety hazard of increased heat generation inside the battery. In view of the defects caused by this structure, through holes or 3D interconnection structures can be added to solve the deficiencies in the conductivity, heat dissipation and bonding of the composite copper foil. In the prior art, a metal film is deposited on a porous PET film with a conical pore by vacuum magnetron sputtering, and then a three-dimensional interconnected copper structure is prepared by electroplating to thicken the copper layer, so as to achieve the effect of improving the conductivity and bonding of the composite copper foil. In order to smoothly metallize the pores during the magnetron sputtering process, the requirement of using conical pores with a large slope and a large aperture not only limits the structure and size of the three-dimensional composite copper foil, but also greatly increases the process complexity. In addition, the preparation process uses large-scale precision instruments, which is relatively costly and limits its industrial application to a certain extent. Summary of the invention

[0007] The present invention proposes a three-dimensional composite copper foil prepared by a formaldehyde-free wet chemical copper plating method and a preparation method thereof. The preparation method is not limited by the structure and size of the three-dimensional composite copper foil, and can prepare a three-dimensional composite copper foil with a firm structure, low resistivity, fast heat dissipation and high safety performance, so as to improve the energy density of the battery cell and enhance the cycle and rate performance of the battery.

[0008] In a first aspect, the present invention provides a three-dimensional composite copper foil prepared based on a formaldehyde-free wet chemical copper plating method, comprising a porous membrane substrate, and a three-dimensional copper structure deposited on the porous membrane substrate;

[0009] The formaldehyde-free wet chemical copper plating method uses sodium hypophosphite as a reducing agent to metallize the surface and pore wall copper of the porous membrane substrate;

[0010] The three-dimensional copper structure includes copper layers distributed on both sides of the porous membrane substrate, and a solid copper structure filled in the pores of the porous membrane substrate and connected to the copper layers;

[0011] The porous membrane substrate has a plurality of pores penetrating along the thickness direction, and the shape of the pores can be straight or curved.

[0012] In some implementations, the material of the porous membrane substrate is selected from polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), polyetherimide (PEI), polypropylene (PP), polyethylene (PE) or polycarbonate (PC).

[0013] In some implementations, the copper layer of the three-dimensional composite copper foil has a thickness of 0.5 to 2.5 μm.

[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned three-dimensional composite copper foil, comprising the following steps:

[0015] S1. irradiating the polymer film with heavy ions, chemically etching the polymer film with an etching solution to obtain a porous membrane substrate having through pores;

[0016] S2. Pretreating the porous membrane substrate and performing formaldehyde-free wet chemical copper plating to obtain a copper metallized porous membrane substrate;

[0017] S3. Perform thickening deposition on the copper metallized porous membrane substrate to thicken the copper layer on its surface, and deposit a solid copper structure connected to the copper layer in the pores to obtain a three-dimensional composite copper foil.

[0018] In some implementations, the heavy ion irradiation in step S1 uses one or more heavy ions with an atomic number greater than or equal to 36, and the irradiation energy is 1 to 30 MeV / u, and the injection amount is 10 4 ~10 8 ions / cm 2 .

[0019] In some implementations, the heavy ions used in the heavy ion irradiation in step S1 are 129 Xe, 124 Sn, 181 or 86 One or more of Kr.

[0020] In some implementations, the polymer film is PET, the etching solution is a NaOH solution, and the molar concentration of the NaOH solution is 1-15M.

[0021] In some implementations, the polymer film is PEN, the etching solution is a NaOH solution, and the molar concentration of the NaOH solution is 1-10M.

[0022] In some implementations, the polymer film is PI or PEI, and the etching solution is a NaClO solution, wherein the mass percentage content of effective chlorine in the NaClO solution is 5-15%, and the pH value of the solution is 8.0-12.0.

[0023] In some implementations, in step S1, the temperature of chemical etching is 15-80°C

[0024] In some implementations, the pretreatment steps in step S2 include chromium pickling, pickling, activation, and formaldehyde-free wet chemical copper plating reaction.

[0025] In some implementations, the plating solution formula used in the formaldehyde-free wet chemical copper plating method includes CuSO4·5H2O, Na3C6H5O7·2H2O, NiSO4·6H2O, H3BO3, and NaH2PO2·H2O.

[0026] As a preferred embodiment, the pretreatment step in step S2 is: the base film is immersed in 5M chromic acid solution for 3 hours and then washed with water, then washed with 0.1M HCl for 10 minutes and then washed with water, and then washed with 0.2g / L Pd 2+ After activating with the activation solution for 2 to 3 hours, the film is washed with water and finally reacted in a formaldehyde-free wet chemical copper plating solution with a pH of 7 to 10 and a temperature of 50 to 70°C for 1 hour. The plating solution formula is: 10g / L CuSO4·5H2O, 23.5g / L Na3C6H5O7·2H2O, 2g / L NiSO4·6H2O, 20g / L H3BO3, and 30g / L NaH2PO2·H2O. The application of copper metallized porous membranes using formaldehyde-free wet chemical copper plating is not limited by the pores and pore sizes of the porous membranes. The solution can freely enter the pores and form copper particles on the film and pore surface.

[0027] In some implementations, the thickening deposition process in step S3 is performed by electroplating, the electroplating anode is a metallized porous membrane substrate, the cathode is a copper sheet, the plating solution is a mixture of CuSO4·5H2O and H2SO4, and the current applied during the electroplating process is 0.1 to 3A / dm 2 .

[0028] Beneficial effects of the present invention:

[0029] The formaldehyde-free chemical copper plating method used in the present invention is combined with the electroplating method to prepare a copper layer on the surface of the porous membrane, and at the same time, solid copper that penetrates the base membrane and connects the upper and lower copper layers is prepared in the pores to obtain a three-dimensional interconnected copper structure, and finally a three-dimensional composite copper foil is obtained; the formaldehyde-free chemical copper plating method used in the present invention uses sodium hypophosphite as a reducing agent, and sodium hypophosphite is low in price, the plating solution is stable, and the reaction conditions are not demanding; the formaldehyde-free chemical copper plating method combined with the electroplating method can accelerate the deposition of copper, and can be assembled into an industrial production line with the electroplating method, replacing the magnetron sputtering link of the physical method, and can effectively save equipment costs and time costs; compared with other preparation processes, the method of combining formaldehyde-free wet chemical copper plating with the electroplating method of the present patent has a simple process, the thickness of the prepared copper foil is uniform and controllable, and no binder is introduced, which is more suitable for industrial production.

[0030] In addition, compared with the three-dimensional composite copper foil and its preparation method in the prior art, the chemical preparation method proposed in this patent is not limited by the pore shape and pore diameter of the porous membrane, and can be applied to straight holes and curved holes with smaller pore sizes.

[0031] The highly interconnected three-dimensional copper structure of the three-dimensional composite copper foil in the present invention can enhance the firmness of the composite structure, avoid the shedding of the metal layer during use, and is beneficial to the long cycle and rate performance of the battery. Compared with the separated two-dimensional copper layers of ordinary composite copper foil, the three-dimensional copper structure of the three-dimensional composite copper foil can enhance the three-dimensional conductivity of the composite copper foil, solve the problems of large surface resistance and difficult three-dimensional conductivity of ordinary composite copper foil, and quickly export the heat inside the battery to the battery shell, avoiding the safety hazard of increased heat generation of the battery, and alleviating the performance degradation caused by heat accumulation inside the battery.

[0032] The formaldehyde-free chemical copper plating method proposed in the present invention provides a new and effective method for the production of composite copper foil, which is beneficial to promoting the development of composite copper foil. In addition, the composite copper foil prepared by this patent has a strong structure, high thermal conductivity, low resistance and high safety performance, which can improve the energy density of the battery cell and improve the cycle and rate performance of the battery, which is beneficial to promoting the development of high energy density batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the preparation process of the three-dimensional composite copper foil of the present invention in a specific embodiment;

[0034] Figure 2a The surface SEM image of the PET base film prepared in Example 1;

[0035] Figure 2b This is a cross-sectional SEM image of the PET base film prepared in Example 1;

[0036] Figure 3 This is a surface SEM image of the copper-metallized PET porous membrane prepared in Example 1;

[0037] Figure 4a This is a cross-sectional SEM image of the three-dimensional composite copper foil prepared in Example 1;

[0038] Figure 4b This is a surface SEM image of the three-dimensional composite copper foil prepared in Example 1;

[0039] Figure 5a This is a cross-sectional SEM image of copper EDS analysis of the three-dimensional composite copper foil prepared in Example 1;

[0040] Figure 5b This is a cross-sectional EDS image of the three-dimensional composite copper foil prepared in Example 1;

[0041] Figure 6a Surface SEM image of the PI porous membrane prepared in Example 2;

[0042] Figure 6b The cross-sectional SEM of the PI porous membrane prepared in Example 2;

[0043] Figure 7 This is a surface SEM image of the copper-metallized PI porous membrane prepared in Example 2;

[0044] Figure 8 This is a cross-sectional SEM image of the three-dimensional composite copper foil prepared in Example 2;

[0045] Figure 9a This is a diagram showing the tape test results of the three-dimensional composite copper foil prepared in Example 1;

[0046] Figure 9b This is a diagram showing the tape test results of the composite copper current collector of Comparative Example 1;

[0047] Fig.10a This is a schematic diagram of the conductivity of the three-dimensional composite copper foil prepared in Example 1 in the thickness direction;

[0048] Fig.10b A schematic diagram of the conductivity of the common composite copper foil in the thickness direction before cutting in Comparative Example 1;

[0049] Fig.10c A schematic diagram of the conductivity of the common composite copper foil of Comparative Example 1 in the thickness direction after cutting;

[0050] Fig.11a This is a thermal conductivity diagram of the comsol simulation of the three-dimensional composite copper foil of Example 2;

[0051] Fig.11b This is a thermal conductivity diagram of the comsol simulated common composite copper foil of comparative example 1;

[0052] Fig.12 The diagram is a test result diagram of the surface density of the copper current collectors of Example 1-2 and Comparative Example 1-2;

[0053] Fig.13 Specific capacity-efficiency diagram for rate cycling of graphite half-cells assembled with different copper current collectors.

[0054] The accompanying drawings are only used for illustrative purposes and should not be construed as limitations on the present invention. In order to better illustrate the present embodiment, some parts of the accompanying drawings may be omitted, enlarged or reduced, and do not represent the size of the actual product. For those skilled in the art, it is understandable that some well-known structures and their descriptions may be omitted in the accompanying drawings. The same or similar reference numerals correspond to the same or similar parts. The terms describing the positional relationship in the accompanying drawings are only used for illustrative purposes and should not be construed as limitations on the present invention. DETAILED DESCRIPTION

[0055] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0056] In view of the large limitations of the existing physical preparation methods of three-dimensional composite copper foil and the problems of structural and dimensional limitations of three-dimensional composite copper foil, the present invention proposes a formaldehyde-free wet chemical copper plating method, which can solve the problems of structural and dimensional limitations of three-dimensional composite copper foil through an environmentally friendly formaldehyde-free chemical copper plating combined with an electroplating preparation method, while improving the conductivity, heat dissipation and composite structure stability of the composite copper foil.

[0057] The formaldehyde-free chemical copper plating method used in the present invention is combined with the electroplating method to prepare a copper layer on the surface of the porous membrane, and at the same time, a solid copper that penetrates the base membrane and connects the upper and lower copper layers is prepared in the hole to obtain a three-dimensional interconnected copper structure, and finally obtain a three-dimensional composite copper foil. The formaldehyde-free chemical copper plating method used in the present invention uses sodium hypophosphite as a reducing agent, which is cheap, has a stable plating solution, and has low requirements for reaction conditions. The formaldehyde-free chemical copper plating method combined with the electroplating method can accelerate the deposition of copper, and can be assembled into an industrial production line with the electroplating method, replacing the magnetron sputtering link of the physical method, which can effectively save equipment costs and time costs. Compared with other preparation processes, the method of combining the formaldehyde-free wet chemical copper plating with the electroplating method of the present invention is simple in process, the thickness of the prepared copper foil is uniform and controllable, and there is no introduction of a binder, which is more suitable for industrial production. In addition, compared with the three-dimensional composite copper foil and its preparation method in the prior art, the chemical preparation method proposed in the present invention is not limited by the pore shape and pore diameter of the porous membrane, and can be applied to straight-through holes and curved holes with smaller pore sizes.

[0058] The three-dimensional composite copper foil prepared by the present invention has a highly interconnected three-dimensional copper structure, which can enhance the firmness of the composite structure, avoid the shedding of the metal layer during use, and is beneficial to the long cycle and rate performance of the battery. Compared with the separated two-dimensional copper layers of ordinary composite copper foil, the three-dimensional copper structure of the three-dimensional composite copper foil can enhance the three-dimensional conductivity of the composite copper foil, solve the problems of large surface resistance and difficult three-dimensional conductivity of ordinary composite copper foil, and quickly export the heat inside the battery to the battery shell, avoiding the safety hazard of increased heat generation of the battery, and alleviating the performance degradation caused by heat accumulation inside the battery.

[0059] Therefore, the formaldehyde-free chemical copper plating method proposed in the present invention provides a new and effective method for the production of composite copper foil, which is beneficial to promoting the development of composite copper foil. In addition, the composite copper foil prepared by the present invention has a strong structure, high thermal conductivity, low resistance and high safety performance, which can improve the energy density of the battery cell and improve the cycle and rate performance of the battery, which is beneficial to promoting the development of high energy density batteries.

[0060] Embodiment 1:

[0061] Take PET as an example of the polymer film material, take a cylindrical through hole as an example of the channel, and take a lithium-ion battery as an example of the application.

[0062] (1) Using the heavy ion accelerator86 Kr ions were used to irradiate PET film with a thickness of 12 μm vertically and uniformly to obtain a PET film with irradiation damage area, wherein the heavy ions 86 The energy of Kr is 25 MeV / u, and the irradiation dose is 1×10 6 ions / cm 2 The PET film after heavy ion irradiation was then chemically etched to obtain a PET porous film with cylindrical straight through holes, wherein the etching solution was 2M NaOH, the etching temperature was 70°C, and the etching time was 127 minutes. The chemically etched PET film was washed with clean water and dried to obtain a PET porous film with circular straight through holes with a pore diameter of about 2.6 μm, which was used as a base film.

[0063] The surface SEM image of the prepared PET base film with cylindrical through-hole structure is shown in Figure 2a As shown in the figure, it can be seen that the pore shape of the biconical pores of the prepared PET base film is clear and the pore size is uniform. The cross-sectional SEM of the prepared cylindrical pore structure of the PET base film is as follows Figure 2b As shown, the thickness of the PET base film after etching is about 9.2 μm, and the hole walls are sharp and vertical.

[0064] (2) Pretreatment and formaldehyde-free wet chemical copper plating were performed on the porous membrane to obtain a copper metallized porous membrane. The pretreatment steps were as follows: the base membrane was immersed in 5M chromic acid for 3 hours and then washed with water, then acid-washed with 0.1M HCl for 10 minutes and then washed with water, and then 0.2g / L Pd 2+ After activation with the activation solution for 2 hours, the sample was washed with water and finally reacted in a formaldehyde-free chemical copper plating solution at 55°C for 1 hour. The plating solution formula was: 10g / L CuSO4·5H2O, 23.5g / L Na3C6H5O7·2H2O, 2g / L NiSO4·6H2O, 20g / L H3BO3, 30g / L NaH2PO2·H2O, and its pH = 8.

[0065] The surface SEM images of the copper-metallized PET base film are shown in Figure 3 As shown, it can be seen that the diameter of the copper particles is about 166nm and the copper particles are evenly distributed. Since the copper particles are small, the application of copper metallized porous membrane using formaldehyde-free wet chemical copper plating is not limited by the pores and pore size of the porous membrane. The solution can freely enter the pores and form copper particles on the surface.

[0066] (3) Electroplating to thicken the copper-clad base film. The copper-metallized PET porous film was used as the cathode and the pure copper sheet was used as the anode. At room temperature (25°C), a current density of 0.16 A / dm 2The copper layer on both sides of the base film was thickened to 1 μm by electroplating, and a solid copper column penetrating the porous film was obtained to obtain a three-dimensional composite copper foil. After the electroplating, the three-dimensional composite copper foil was washed with deionized water and dried.

[0067] The cross-sectional SEM images and surface SEM images of the three-dimensional composite copper foil prepared in this example are shown in FIG. Figure 4a and Figure 4b As shown in FIG. 1 , the total thickness of the three-dimensional composite copper foil is about 11.2 μm, of which the thickness of the copper layer on the surface is about 1 μm, the edges of the cylindrical copper structure are clear, the structure is compact, the copper column and the copper layer are interconnected, and the copper structure is a three-dimensional structure. The cross-sectional SEM image of the three-dimensional composite copper foil of this example and the EDS analysis image of the copper element are shown in FIG. Figure 5a and Figure 5b As shown, it can be seen that the element of the cylindrical structure is copper, which further confirms that the hole can be fully plated with copper pillars, and the copper pillars and the copper layer are interconnected three-dimensional structures.

[0068] Embodiment 2:

[0069] The three-dimensional composite copper foil of this embodiment has a base film of PI film, and the hole channel is a cylindrical through hole as an example. The preparation steps are as follows:

[0070] (1) Using the heavy ion accelerator 129 The PI film with a thickness of 7.5 μm was vertically and uniformly irradiated in Xe ions, and the heavy ions 129 The energy of Xe is 19.55 MeV / u, and the irradiation dose is 5×10 6 ions / cm 2 Then, the PI film irradiated with heavy ions was placed in an etching solution (the etching solution was a NaClO solution with an effective chlorine content of ≥10%) and etched in a 70°C water bath for 180 minutes; after etching, the PI film was washed with clean water and dried naturally to obtain a PI porous membrane with a cylindrical through-hole structure.

[0071] The surface SEM images and cross-sectional SEM images of the prepared PI porous membrane with cylindrical through pores are shown in Figure 2. Figure 6a and Figure 6b As shown, it can be seen that the cylindrical through pores of the prepared PI porous membrane have uniform pore diameters, with a pore diameter of about 1.8 μm and a thickness of about 4.5 μm.

[0072] (2) Pretreatment and formaldehyde-free wet chemical copper plating were performed on the PI porous membrane to obtain a copper metallized base membrane. The pretreatment steps were: the base membrane was immersed in 5M chromic acid for 3 hours and then washed with water, then acid-washed with 0.1M HCl for 10 minutes and then washed with water, and then 0.2g / L Pd 2+After activation with the activation solution for 2 hours, the sample was washed with water and finally reacted in a formaldehyde-free chemical copper plating solution at 70°C for 1 hour. The plating solution formula was: 10g / L CuSO4·5H2O, 23.5g / L Na3C6H5O7·2H2O, 2g / L NiSO4·6H2O, 20g / L H3BO3, 30g / L NaH2PO2·H2O, and the reaction conditions were pH=7-10, temperature of 60°C, and pH=8.

[0073] The surface SEM image of the copper metallized PET base film is as follows: Figure 7 As shown, it can be seen that the copper particle layer tightly and evenly covers the surface of the film.

[0074] (3) Electroplating to thicken the copper-clad base film. The above-mentioned PET porous film was used as the cathode and the pure copper sheet was used as the anode. At room temperature (25°C), a current density of 0.16 A / dm 2 The copper layer on both sides of the base film was thickened to 1 μm by electroplating, and a solid copper column penetrating the porous film was obtained to obtain a three-dimensional composite copper foil. After the electroplating, the three-dimensional composite copper foil was washed with deionized water and dried.

[0075] The cross-sectional SEM image of the three-dimensional composite copper foil prepared in this example is as follows: Figure 8 As shown, it can be seen that the total thickness of the three-dimensional composite copper foil is about 6.3 μm, of which the copper thickening layer is 0.7 μm, and the cylindrical copper structure is complete and tight.

[0076] Comparative Example 1:

[0077] Commercial composite copper foil A from Company A was purchased as comparative example 1. The commercial composite copper foil A was prepared by a "two-step method", that is, a layer of metal copper with a thickness of less than 100 nm was magnetron sputtered on the surface of the PET film to metallize the film, and then the copper layer was thickened to 1 μm by water electroplating. The total thickness of the commercial composite copper foil A was 6.5 μm, and the structure was a "sandwich" structure, in which the polymer layer was made of PET with a thickness of 4.5 μm, and the thickness of the copper layer on both sides was 1 μm.

[0078] Comparative Example 2:

[0079] A double-sided copper foil with a thickness of 9 μm was used as comparative example 2, and its weight density was 86 g / m 2 .

[0080] Embodiment 3:

[0081] This example provides a sample tape peeling test experiment:

[0082] The composite copper foils of Example 1 and Comparative Example 1 were covered with Chenguang tape, and then the tapes were peeled off after rolling with a stainless steel column. The peeling results were as follows: Figure 9a and Figure 9b As shown in the figure, the copper layer on the surface of the three-dimensional composite copper foil did not fall off after the tape stripping test, while the copper layer on the surface of the ordinary composite copper foil was stripped by the tape. Since the structure of the ordinary composite copper foil is mainly composited by intermolecular forces, the metal layer is easily separated from the polymer film, resulting in electrode failure. The copper layers on the upper and lower surfaces of the three-dimensional composite copper foil are connected by a dense solid copper structure in the middle. The metal bond is stronger than the intermolecular force, so the composite structure of the three-dimensional composite copper foil is more solid.

[0083] Embodiment 4:

[0084] This embodiment provides a conductivity test experiment:

[0085]

[0086] Table 1: Resistance of different samples in the vertical direction

[0087] The resistance on both sides of the current collector is measured to qualitatively evaluate the conductivity of the current collector in the vertical direction. Among them, the resistance measurement results of different copper foil samples of Examples 1-2 and Comparative Examples 1-2 on the film surface and in the film thickness direction are shown in Table 1. It can be seen from Table 1 that the resistance value of the three-dimensional composite copper foil of Examples 1-2 in the thickness direction is not affected by cutting, and the resistance measurement values ​​are all less than 0.1Ω. The ordinary composite copper foil of Comparative Example 1 before cutting is not conductive in the vertical direction, and the ordinary composite copper foil of Comparative Example 1 after cutting has a larger resistance measurement value in the thickness direction. This is because the three-dimensional copper structure of the three-dimensional composite copper foil provides a large number of internal conductive channels, so its electron transmission speed in the thickness direction is faster (such as Fig.10a Ordinary composite copper foil can only transmit electrons through the surface copper layer before cutting (such as Fig.10b As shown in the figure, the cut ordinary composite copper foil has the ability to conduct electricity in the thickness direction only through the metal transmission electrons in contact with the edge (as shown in the figure). Fig.10c Compared with the dense internal electron transport paths of the three-dimensional composite copper foil (as shown in Fig.10c As shown in the figure, the transmission path of ordinary composite copper foil is long and less, so the resistance value in the thickness direction is still large after cutting. Compared with the existing composite copper foil, the three-dimensional composite copper foil shows better conductivity, which is beneficial to improve the rate performance of the battery. However, the poor conductivity of ordinary composite copper foil in the thickness direction is not conducive to its direct application in button batteries and soft-pack batteries. It needs to be processed later to make it conductive in the thickness direction before it can be used in batteries. For example, the existing composite copper foil needs to be transferred to the soft-pack battery before it can be used.

[0088] Embodiment 5:

[0089] This embodiment provides a thermal conductivity test experiment:

[0090] Comsol is used to simulate the heat transfer behavior of Example 2 and Comparative Example 1 models after contacting the heat source (the model parameters are thickness, material thermal conductivity, and heat transfer equation). The simulated heat conduction processes are as follows: Fig.11a and 11b As shown, the heat of ordinary composite copper foil cannot be quickly discharged after contacting the heat source. The middle of the ordinary composite current collector is a polymer block material with low thermal conductivity. There is no channel for rapid heat dissipation inside, and the heat dissipation capacity is low. However, the three-dimensional composite copper foil has a copper material with high thermal conductivity in the middle. The copper material that runs through the polymer film provides a large number of heat conduction channels and has a stronger heat dissipation capacity. When the temperature inside the battery rises, the three-dimensional composite copper foil can quickly discharge the temperature, which can alleviate the deterioration of the internal environment of the battery caused by the accumulation of heat inside the battery, and avoid the safety hazard of increased heat generation of the battery.

[0091] Embodiment 6:

[0092] This embodiment provides a surface density test experiment

[0093] The three-dimensional composite copper foil of Example 2, the commercial composite copper foil of Comparative Example 1, and the pure copper foil of Comparative Example 2 were tested for surface density. The surface density test results of different copper foil samples are as follows: Fig.12 As shown. The surface density of the three-dimensional composite copper foil is 3.54g / cm 2 The surface density of the two common composite copper foils is 2.5g / cm 2 With 2.7g / cm 2 The solid copper structure in the middle of the three-dimensional composite increases some weight, resulting in the surface density of the three-dimensional composite copper foil being slightly higher than that of ordinary composite copper foil. However, the surface density of the three-dimensional composite copper foil is only 40.4% of that of pure copper foil. The three-dimensional composite copper foil can effectively reduce the weight of the current collector.

[0094] Embodiment 7:

[0095] This embodiment provides a charge and discharge performance test experiment:

[0096] The three-dimensional composite copper foil of Example 2 and the pure copper foil of Comparative Example 2 were coated with graphite slurry (fast-charging graphite: super-P: PVDF = 8:1:1) and cut into discs with a diameter of 16 mm after being fully dried, and the discs were used as battery poles; the ordinary composite copper foil was first cut into discs with a diameter of 16 mm, then coated with graphite slurry, and used as battery poles after being fully dried. Finally, several battery poles were assembled into graphite-lithium button batteries, and the batteries were cycled 5 times at different rates. The rate cycle curves are shown in FIG. Fig.13 As shown. Fig.13 It can be seen that the rate cycling performance of several button cells is similar, and the specific capacity of the composite copper foil is higher.

[0097] It should be noted that the above embodiments illustrate the present invention rather than limit the present invention, and those skilled in the art may design alternative embodiments without departing from the scope of the appended claims. In the claims, any reference symbol between brackets shall not be construed as a limitation to the claims.

[0098] In combination with Examples 3-7, it can be seen that the three-dimensional composite copper foil based on the base film with cylindrical straight-through channels and the three-dimensional interconnected copper structure proposed in the present invention significantly improves the stability, conductivity, thermal conductivity and other safety performance of the composite structure of the composite copper foil, improves the cycle and rate performance of the battery, and the preparation method of formaldehyde-free wet chemical copper plating combined with electroplating is more suitable for industrial production, which solves the problems of commercial composite copper foil composite structure, poor conductivity and heat dissipation, and high industrialization barriers, and is conducive to promoting the development of high energy density batteries.

[0099] Embodiment 8:

[0100] This embodiment provides a current collector, including the three-dimensional composite copper foil prepared by the formaldehyde-free wet chemical copper plating method in the above embodiment.

[0101] In the description provided herein, a large number of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. Similarly, in order to simplify the present invention and help understand one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, the various features of the embodiments of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. Wherein, the claims that follow the specific embodiment are hereby expressly incorporated into the specific embodiment, wherein each claim itself is a separate embodiment of the present invention.

[0102] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A three-dimensional composite copper foil prepared by a formaldehyde-free wet chemical copper plating method, characterized in that: It includes a porous membrane substrate, and a three-dimensional copper structure deposited on the porous membrane substrate; The three-dimensional copper structure includes copper layers distributed on both sides of the porous membrane substrate, and a solid copper structure filled in the pores of the porous membrane substrate and connected to the copper layers; The porous membrane substrate has a plurality of pores penetrating along the thickness direction, and the shape of the pores can be straight or curved.

2. The three-dimensional composite copper foil prepared by the formaldehyde-free wet chemical copper plating method according to claim 1, characterized in that: The material of the porous membrane substrate is selected from polyethylene terephthalate, polyethylene naphthalate, polyimide, polyetherimide, polypropylene, polyethylene or polycarbonate.

3. The three-dimensional composite copper foil prepared by the formaldehyde-free wet chemical copper plating method according to claim 1, characterized in that: The copper layer thickness of the three-dimensional composite copper foil is 0.5-2.5 μm.

4. A method for preparing the three-dimensional composite copper foil according to any one of claims 1 to 3, comprising the following steps: S1. irradiating the polymer film with heavy ions, chemically etching the polymer film with an etching solution to obtain a porous membrane substrate having through pores; S2. Pretreating the porous membrane substrate and performing formaldehyde-free wet chemical copper plating to obtain a copper metallized porous membrane substrate; S3. Perform thickening deposition on the copper metallized porous membrane substrate to thicken the copper layer on its surface, and deposit a solid copper structure connected to the copper layer in the pores to obtain a three-dimensional composite copper foil.

5. The preparation method according to claim 4, characterized in that: The heavy ion irradiation in step S1 uses one or more heavy ions with an atomic number greater than or equal to 36, and the irradiation energy is 1 to 30 MeV / u, and the injection amount is 10 4 ~10 8 ions / cm 2 .

6. The preparation method according to claim 5, characterized in that: The heavy ions used in the heavy ion irradiation in step S1 are 129 Xe, 124 Sn, 181 or 86 One or more of Kr.

7. The preparation method according to claim 4, characterized in that: The polymer film is PET, the etching solution is NaOH solution, and the molar concentration of the NaOH solution is 1-15M.

8. The preparation method according to claim 4, characterized in that: The polymer film is PEN, the etching solution is NaOH solution, and the molar concentration of the NaOH solution is 1-10M.

9. The preparation method according to claim 4, characterized in that: The polymer film is PI or PEI, and the etching solution is a NaClO solution, wherein the mass percentage content of effective chlorine in the NaClO solution is 5-15%, and the pH value of the solution is 8.0-12.

0.

10. The preparation method according to claim 5, characterized in that: In step S1, the temperature of chemical etching is 15-80°C.

11. The preparation method according to claim 4, characterized in that: The pretreatment steps in step S2 include chromium pickling, pickling, activation and formaldehyde-free wet chemical copper plating reaction.

12. The preparation method according to claim 11, characterized in that: The plating solution formula used in the formaldehyde-free wet chemical copper plating method includes CuSO4.5H2O, Na3C6H5O7.2H2O, NiSO4.6H2O, H3BO3, and NaH2PO2.H2O.

13. The preparation method according to claim 4, characterized in that: The thickening deposition process in step S3 adopts electroplating, the electroplating anode is a metallized porous membrane substrate, the cathode is a copper sheet, the plating solution is a mixture of CuSO4·5H2O and H2SO4, and the current applied during the electroplating process is 0.1-3A / dm 2 .